2014
DOI: 10.4236/oalib.1100734
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Anomalies in Fetus with Neural Tube Defects

Abstract: Background: The objective of this study is to analyze the incidence of congenital urogenital malformations in human fetuses with neural tube defects (NTDs). Methods: We studied 320 human fetuses (214 males and 106 female) ranged in age from 12 to 35 weeks post-conception (WPC). The fetuses were carefully dissected with the aid of a stereoscopic lens with 16/25× magnification. The abdomen and pelvis were opened to identify and expose the urogenital organs. We studied the incidence of renal, ureteral, bladder, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, Costa et al ( 27 ) studied 17 human fetuses with NTDs and found that urogenital anomalies in human fetuses with NTDs are significant, with an incidence greater than 20%, but did not find severe urogenital anomalies that impair body function. The same group reported that in fetuses with anencephaly, the ureters had smaller diameter, area and thickness, which could indicate that this tissue tends to have significant structural alterations, probably due to cerebral lesions with consequent brain control damage of ureter nerves ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Costa et al ( 27 ) studied 17 human fetuses with NTDs and found that urogenital anomalies in human fetuses with NTDs are significant, with an incidence greater than 20%, but did not find severe urogenital anomalies that impair body function. The same group reported that in fetuses with anencephaly, the ureters had smaller diameter, area and thickness, which could indicate that this tissue tends to have significant structural alterations, probably due to cerebral lesions with consequent brain control damage of ureter nerves ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral duplication was an associated finding in a study by SF Costa et al 20 Previous studies showed cystic kidney in cranioschisis. Double ureters were found in one case of craniorachischisis and one case of occipital encephalocele (15.38%).…”
Section: However Nakatsu Et Al (2000) Observed 3 Sites Ofmentioning
confidence: 93%